ASSESSMENT OF THE THERMAL MATURATION OF POSSIBLE HYDROCARBON SOURCE ROCKS FROM THE LOWER CRETACEOUS BIMA FORMATION, NORTHERN BENUE TROUGH, NORTH EAST NIGERIA - Saidu, Fatima; Maigari, Abubakar Sadiq; Umar, Bappah Adamu; Aliyu, Abdulkarim Haruna; Jibrin, Abdulmajid Isah; Umar, Umar Sambo (FUDMA JOURNAL OF SCIENCES, 2025)
The oldest sedimentary unit in the Northern Benue Trough is the Early Cretaceous Bima Formation. This research is aimed at studying the sedimentary successions in Bima Formation in the Yola Basin with a view to understanding its hydrocarbon source rock maturity using palynological analysis with the aim to provide an overview of the type, quality and maturity of organic matter using spore coloration index and to examine the processes controlling organic matter enrichment in the sediments from subsurface data. One hundred and fifty (150) samples of shales, sandstone, siltstone and mudstone were subjected to palynological analysis using standard palynological preparation techniques. Visual color analysis was later carried out on the recovered palynomorphs. Microscopic analysis of the differences in spore and pollen color was performed on sporomorphs found in the samples. From the samples studied, the C.A.I (Colour Alteration Index) and T.A.I (Thermal Alteration Index) which ranges from 1.5-3.5 in conjunction with corresponding vitrinite reflectance of %R0 =2-3.5 suggesting the catagenetic stage and temperatures more than 120 °C, reveal that the source rocks of the Bima Formation in the Yola Basin are immature to very mature occurring within the oil and dry gas limit of hydrocarbon production. Though poor in sporomorph content, show indications of organic matter that is good to excellent quality with Kerogen type II and III as the main organic matter type present. When exposed to burial temperatures ranging from 60°C to 160°C, Type II and III kerogen produce the majority of the world’s oil and gas.